The films of Lenny Abrahamson a filmmaking of philosophy - Monahan, Barry 1973- (Bloomsbury Academic, 2018)
"A thorough reflection on the stylistic and philosophically-profound cinematic work of Ireland's most exciting contemporary directors, Lenny Abrahamson"...